2015
DOI: 10.1063/1.4918669
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to laser machining of silicon using femtosecond micro-Bessel beams in the infrared

Abstract: We produce and characterize high-angle femtosecond Bessel beams at 1300-nm wavelength leading to nonlinearly ionized plasma micro-channels in both glass and silicon. With microjoule pulse energy, we demonstrate controlled through-modifications in 150-lm glass substrates. In silicon, strong two-photon absorption leads to larger damages at the front surface but also a clamping of the intensity inside the bulk at a level of %4 Â 10 11 W cm À2 which is below the threshold for volume and rear surface modification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of Si subsurface modification with a femtosecond laser without altering the wafer surface. We overcome previously reported difficulties in direct-laser processing of Si below the surface [19,20] by benefiting from cumulative effects arising from the use of high repetition rates (250 kHz), in a manner that is loosely analogous to [24]. We furthermore provide clear evidence that the structures are indeed waveguiding, tested at 1.5 μm telecommunication wavelength.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report of Si subsurface modification with a femtosecond laser without altering the wafer surface. We overcome previously reported difficulties in direct-laser processing of Si below the surface [19,20] by benefiting from cumulative effects arising from the use of high repetition rates (250 kHz), in a manner that is loosely analogous to [24]. We furthermore provide clear evidence that the structures are indeed waveguiding, tested at 1.5 μm telecommunication wavelength.…”
mentioning
confidence: 61%
“…The lack of functional waveguides or, in general, in-chip devices is due to difficulties in 3D laser processing of Si without altering the wafer surface [19,20]. We have first shown the possibility of laser processing deep inside Si using nanosecond pulses at 1.55 μm [21], where Si is transparent.…”
mentioning
confidence: 99%
“…The direct ablation process with short [1,2] and ultrashort laser pulses [3][4][5][6] allows the well-defined drilling of different materials like dielectrics, polymers, semiconductors, and metals. Especially the usage of fs laser radiation allows the fabrication of holes in dielectric surfaces with diameters in the sub-m range with a high aspect ratio [7][8][9] using Bessel beams. Furthermore, the laser drilling in dielectric surfaces can be assisted by a wet chemical etching process, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in case of Si microstructuring using Bessel beams, the wavelength of the fs laser should be longer than 1.13 μm, since the band gap of Si is 1.12 eV. However, even fs lasers operating in the transparent window of Si cannot easily perform deep etching of Si due to its narrow band gap, strong two-photon absorption, and weak free carrier absorption2728293031. Moreover, it has been recently reported that there are inherent limitations for the volume and rear surface modification of Si when using 1.3-μm fs Bessel beams30.…”
mentioning
confidence: 99%